Study of Rn-222 emanations from fabricated composite brick based on treated oil palm fibre - Mocktar, Nurfarah Aini (2018)
In this thesis, Radon Monitor Sentinel 1030 was used to determine the average concentration of Rn-222 on 3 fabricated composite bricks with different composition of cement, stone and sand. This study was aimed at making composite bricks based on oil palm fiber to identify the amount of radon concentrations in composite bricks with different composition of raw materials where composite brick 1 had less sand, composite brick 2 had less rock and composite brick 3 reduction in composition of cement. Prior to that, radon gas concentrations reading for raw materials such as stone, sand. cement and Perspex box were taken for 24 hours with 48 data to determine the level of radon gas concentration in the different composition of the raw material. Sodium hydroxide is used to treat the fibre to increase it mechanical strength. In addition, this study was also conducted to identify the mechanical strength of the composite brick by performing compression tests. Concrete brick has the highest force that is 50494N compare to fabricated composite 3 that has the lowest force that is 13676N. The composite brick is placed in the Perspex box to ensure it not exposed to radon gas. The reading was taken for consecutive 3 days with a total of 144 data for one composite brick. This study focuses on which material contributes to higher levels of radon concentrations whether sand, cement or stone. In addition, the radon concentration level is also influenced by pressure, temperature and humidity or more suitable to be called weather. Based on the data obtained, composite bricks with the highest concentration of radon were composite bricks 2 where the major contributor to the increase in radon concentration was stone. Concrete bricks have lower levels of radon concentrations than composite bricks where fibers have high carbon levels and are a good absorption material for water and increase humidity levels in composite bricks and cause composite bricks to have higher radon readings than concrete brick. By reducing material that has high levels of radon on the use of fiber, it indirectly reduces the composition of raw materials to make bricks while reducing the cost of buying large raw materials.